Estudos bioquímicos e cinéticos de acetilcolinesterases de formigas cortadeiras (Atta sexdens) - Santos, Adriana Miranda dos (Universidade Federal de São Carlos, 2017)
Acetylcholinesterase (AChE) (EC 3.1.1.7) is the enzyme responsible for catalyzing the hydrolysis of the neurotransmitter acetylcholine leading to the release of acetate and choline. In insects, acetylcholine is one of the most important neurotransmitters, and inhibition of AChE produces a generalized synaptic collapse causing the insect death. AChE is, thus, an important target for the development of new insecticides. In this context, this work describes the results obtained in the production of the active recombinant enzyme, expressed in Pichia pastoris and obtained through the gene coding for AChE of A. sexdens, cloned in the pPICZα-A vector. By sequencing the positive clone the sequence of the recombinant AChE was obtained and, by homology, a three-dimensional model was constructed and validated. In addition, this work presents, for the first time, the isolation, purification and biochemical characterization of two native AChE from Atta sexdens (AsAChE-A and AsAChE-B). The kinetic constants were determined using the colorimetric method with the enzymes in solution and acetylthiocholine as the substrate. The isolated enzymes were immobilized on fused silica capillary to produce AsAChE-A and AsAChE-B IMER. IMER activities were measured by quantification of the hydrolysis product of acetylcholine by zonal bioaffinity chromatography with mass spectrometry detection (LC-MS) to produce Michaelis-Menten constants. The differences in affinity for the substrates used: acetylthiocholine (colorimetric method) and acetylcholine (LC-MS) reveal AsAChE-B as the enzyme with the highest affinity for the natural substrate, a result confirmed, also, by measuring choline production with the enzyme in solution. The screening assay was validated using tacrine and galantamine as standard inhibitors of AChE, and the IMERs produced were used for screening inhibitors in a synthetic hydantoin (n = 12) collection. The results presented in this work show the importance of the use of acetylcholine (natural substrate) in AChE activity and inhibition assays.
Biochemistry and kinetic studies of acetylcholinesterase of leaf-cutting ants
Keywords: Acetilcolinesterase; Atta sexdens; Imobilização em Capilar; Inibidores; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOQUIMICA DOS MICROORGANISMOS; CIENCIAS BIOLOGICAS::BIOQUIMICA::ENZIMOLOGIA; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS